Is the (Mass) Party Really Over? The Case of the Dutch Forum for Democracy - de Jonge, Léonie (2021)
Over the past decades, the Netherlands has witnessed the rise of several influential populist radical right parties, including the Pim Fortuyn List (Lijst Pim Fortuyn), Geert Wilders’s Party for Freedom (Partij voor de Vrijheid) and, more recently, the Forum for Democracy (Forum voor Democratie [FvD]). By analyzing the party’s organizational structures, this article seeks to determine whether the FvD may be considered a new “mass party” and to what extent ordinary members can exert influence over the party’s internal procedures. The party’s efforts to establish a large membership base suggest that the FvD set out to build a relatively complex mass organization. Through targeted advertising campaigns, the party made strategic use of social media platforms to rally support. Thus, while the means may have changed with the advent of the internet, the FvD invested in creating some organizational features that are commonly associated with the “mass party” model. At the same time, however, the party did not really seek to foster a community of loyal partisan activists among its membership base but instead treated its members as donors. The party is clearly characterized by centralized leadership in the sense that the party’s spearhead, Thierry Baudet, maintains full control over key decision-making areas such as ideological direction, campaigning, and internal procedures. At first sight, the party appears to have departed from Wilders’s leader-centered party model. However, a closer look at the party apparatus demonstrates that the FvD is, in fact, very hierarchical, suggesting that the party’s internal democracy is much weaker than the party’s name might suggest.